Characterization of coffee grounds as biosorbent for removal dyes from aquaeous solutions. (September 2019) - Mukti, N. I. F.; Hidayat, A.
Abstract: Low cost and effective biomass wastes may have ample applications in water decontamination procedures. Coffee waste is one of the most populer were used as low cost adsorbents for the removal of dyes from aqueous solutions. The aim of this research is to study the effect of washing the coffee residue for dyes adsorption. The characterization functional group of adsorbents was characterized with FTIR, and proximate analysis. The experimental data obtained in the present study indicate that coffee grounds are suitable for use as biosorbents in the removal of dyes.